Patterns of Self-Organization in Search of Recategorization Applied to Dwelling (Palimpsesto, 2021)
The self-organization of housing is understood as a phenomenon studied from the complex systems and approached from the perspective of the generation of housing build by those who doesn´t have the option of improve better conditions to live.This article is developed through the analysis of patterns identified in the texts of different authors understood as a constructive categories and adaptive typologies. To correlate different visions of living and from the phenomenology of the use of space through time and the natural place.The result is a recategorization of these patterns brought to the contemporaneity to understand the role of this type of housing in Latin American cities.
Keywords: Self-housing; patterns; dwelling; self-organization; household